Taxonomic revision of the Neotropical water snake Hydrops triangularis (Serpentes, Colubridae) - de Albuquerque, Nelson R; de Lema, Thales (Zootaxa, 2008)
Six subspecies of Hydrops triangularis (Wagler 1824) are currently recognized on the basis of differences in the number of ventral and subcaudal scales and dorsal coloration (viz., the number of bands on the body, the extent of bands on the body, and the occurrence of projections of the bands on the body). Analysis of a larger sample from throughout the distribution of the species revealed overlapping variation in all of these characters across regional boundaries. The available evidence is therefore unable to objectively delimit multiple geographic races, and we therefore consider the subspecies of H. triangularis to be subjective synonyms.